Concentration and distribution of macrominerals in tissues of Mediterranean mussel Mytilus galloprovincialis exposed to Cd and Cd-mixtures - García-Navarro, José A.; Vera-Sánchez, Miguel A.; Romero, Diego (Revista de Biología Marina y Oceanografía, 2021)
Marine ecosystems are under great pressure due to heavy metals pollution, and mussels remain an important knowledge source in this regard. In this study, Mediterranean mussels (Mytilus galloprovincialis) were exposed for 7 days to Cd and three Cd-mixtures (Cd+Pb, Cd+Cu and Cd+Pb+Cu). The accumulation and tissue distribution of inorganic elements (Ca, K, Mg, Na, P and S, macrominerals) that are usually not taken into consideration in field studies on in bioassays were evaluated. Regarding concentration, the element which differed the most with respect to the control group was K, while Mg was the only one which showed no significant statistical difference with the control group. The group exposed to ternary mixture was the one in which there were more alterations in concentration and distribution of these macrominerals with respect to control, whereas in the group exposed to single Cd no significant differences in the concentration of these inorganic elements were found. The concentration and distribution of macrominerals in the compartments studied (digestive gland, gill and remaining soft tissues) is susceptible to the presence of Cd and heavy metal Cd-mixtures, with percentages of changes until 28.7%. Study results suggest that macrominerals composition in mussel tissues could be useful in studies of heavy metal contamination in marine ecosystems.